2012
DOI: 10.1080/09540121.2012.720362
|View full text |Cite
|
Sign up to set email alerts
|

Internalized stigma and HIV status disclosure among HIV-positive black men who have sex with men

Abstract: Black men who have sex with men (BMSM) are severely affected by the HIV epidemic, yet research on the relationship between HIV stigma and status disclosure is relatively limited among this population. Within this epidemic, internalized HIV stigma, the extent to which people living with HIV/AIDS (PLWHA) endorse the negative beliefs associated with HIV as true of themselves, can negatively shape interpersonal outcomes and have important implications for psychological and physical health. In a sample of HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 24 publications
(24 reference statements)
7
61
0
Order By: Relevance
“…Nondisclosure of one's positive HIV status has been associated with internalized stigma-negative feelings towards oneself because of HIV positive status. Stigma makes some PLHIV remain silent, alienate themselves, and opt not to enroll in health care services, or hide their antiretroviral drugs (ARVs) from others even when they are faced with life threatening health conditions [11]. In a recent study in rural Nigeria, researchers found a strong association between levels of stigma and adherence to ART.…”
Section: Introductionmentioning
confidence: 97%
“…Nondisclosure of one's positive HIV status has been associated with internalized stigma-negative feelings towards oneself because of HIV positive status. Stigma makes some PLHIV remain silent, alienate themselves, and opt not to enroll in health care services, or hide their antiretroviral drugs (ARVs) from others even when they are faced with life threatening health conditions [11]. In a recent study in rural Nigeria, researchers found a strong association between levels of stigma and adherence to ART.…”
Section: Introductionmentioning
confidence: 97%
“…Shame about one’s HIV status can make HIV status disclosure difficult (Chaudoir, Fisher, & Simoni, 2011) and can influence decisions to seek out social support (Chesney, 1999). Internalized stigma is also associated with less frequent disclosure of HIV status to sexual partners (Overstreet, Earnshaw, Kalichman, & Quinn, 2013), increasing risk of HIV transmission. There are also established relationships between stigma and poor HIV outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, PLWH who have experienced HIV self-stigma may be less likely to disclose their HIV status to sex partners (Chaudoir, Fisher, & Simoni, 2011). Several studies demonstrate that HIV self-stigma is associated with a decreased likelihood of disclosure of HIV status to sex partners (Kingori et al, 2012; Overstreet, Earnshaw, Kalichman, & Quinn, 2012; Simbayi et al, 2006). Some, but not all, studies further find an association between status disclosure and unprotected sex (Crepaz & Marks, 2002).…”
Section: Introductionmentioning
confidence: 99%